How Authentic Leadership Influences Team Performance: The Mediating Role of Team Reflexivity - Lyubovnikova, Joanne (Journal of business ethics, 2017)
This study examines how authentic leadership influences team performance via the mediating mechanism of team reflexivity. Adopting a self-regulatory perspective, we propose that authentic leadership will predict the specific team regulatory process of reflexivity, which in turn will be associated with two outcomes of team performance, effectiveness and productivity. Using survey data from 53 teams in three organizations in the United Kingdom and Greece and controlling for collective trust, we found support for our stated hypotheses with the results indicating a significant fully mediated relationship. As predicted the self-regulatory behaviors inherent in the process of authentic leadership served to collectively shape team behavior, manifesting in the process of team reflexivity, which, in turn, positively predicted team performance. We conclude with a discussion of how this study extends theoretical understanding of authentic leadership in relation to teamwork and delineate several practical implications for leaders and organizations.